The prevalence of malaria at first antenatal visit in Blantyre, Malawi declined following a universal bed net campaign. (December 2015) - Boudová, Sarah; Divala, Titus; Mawindo, Patricia; Cohee, Lauren; Kalilani-Phiri, Linda; Thesing, Phillip; Taylor, Terrie; Laufer, Miriam
Abstract Background Preventing malaria during pregnancy is important for the health of mothers and newborns. Interventions, which include distribution of bed nets and administration of intermittent preventive treatment (IPT), typically occur at the first antenatal visit, usually in the second or third trimester of pregnancy. In 2012, during the course of ongoing clinical studies of malaria among pregnant women in Malawi, a universal bed net campaign was implemented by the Government. This study tested the hypothesis that a universal bed net campaign would decrease the prevalence of malaria among pregnant women at their first antenatal visit. Methods Some 1661 women were recruited for two studies from 2009 to 2014. Quantitative PCR (qPCR) was conducted from dried blood spots collected at the first antenatal care visit (prior to administration of IPT or any study interventions) from women who were in their first or second pregnancy and less than 28 weeks gestation by clinical assessment. Results Overall, 320 of 1629 (19.6 %) women tested for malaria at their first antenatal visit were infected. Malaria infection rates declined from 28.4 % before the universal bed net campaign, to 18.5 % in 2012, to 15.0 % in the years following the universal bed net campaign. The odds of malaria infection at the time of first antenatal visit in 2012 and the years following the bed net campaign were significantly lower than in the years prior to the intervention (OR 0.6, 95 % CI 0.4–0.8; and OR 0.4, 95 % CI 0.3–0.6, respectively). A similar pattern was observed for the prevalence of clinical malaria. The inverse trend was observed for reported bed net use. However bed net use and malaria infection were not significantly associated on the individual level. Conclusions Malaria infection in pregnant women is common even after a bed net campaign in Malawi, though prevalence rates declined. These early infections may cause maternal anaemia and placental malaria resulting in adverse maternal and fetal outcomes. Infection early in pregnancy may also contribute to malaria transmission as pregnant women represent a significant untreated reservoir of parasites. Universal bed net distribution appears to have moderate success in preventing malaria early in pregnancy and these findings support continued efforts to target women early in pregnancy and all women of childbearing age.